Seismic Isolation: An Effective Technique for the Seismic Retrofitting of a Reinforced Concrete Building. Issue 1 (2nd January 2020) - Giarlelis, Christos; Koufalis, Dimitrios; Repapis, Constantinos
Abstract: Seismic isolation, usually applied for new structures, is used for the seismic upgrade of a five-storey reinforced concrete building. The building is a frame structure, representative of the residential buildings designed in the 1960s and 1970s in Greece and southern Europe, and thus following an older generation of codes. Response spectrum analysis, performed for the seismic assessment of the structure, using EC8 code provisions, showed poor structural performance and inadequate capacity of many structural members. A seismic upgrade of the structure is thus needed and the use of friction-pendulum system bearings, placed above the foundation level, is examined. A series of linear and non-linear analyses is performed and the results show a major improvement in the overall seismic performance of the building, while interventions are required only at the ground floor and foundation levels. The effectiveness and limitations in the applicability of this retrofitting procedure are discussed. It is concluded that the seismic retrofitting of existing buildings through the use of seismic isolation is an effective approach. It results in an enhanced performance level compared to conventional approaches; therefore, it should always be considered as an alternative to conventional retrofitting techniques.